Using stakeholders' preference for ecosystems and ecosystem services as an economic basis underlying strategic conservation planning. Issue 12 (December 2020) - Ureta, J. Carl; Vassalos, Michael; Motallebi, Marzieh; Baldwin, Robert; Ureta, Joan
Abstract: Ecosystem services (ES), commonly defined as the benefits people get from ecosystems, are key components in improving human well-being. However, as land utilization transitions from forest and agricultural land to urban areas and industrial complexes, the continuous provision of ES is affected. To ensure sustainable development, conservation programs should be implemented that consider both the stakeholders' well-being while also maintaining ecosystem health and integrity. Consequently, to improve the strategic implementation of conservation programs, it is critical to understand stakeholders' preferences. Using an online survey, we elicited South Carolina residents' preference in prioritizing the target ecosystems and ecosystem services in the state. The results identified that the priority ecosystem service is water quality regulation. However, the residents' preference for water quality regulation does not discredit the importance of maintaining the continuous water supply provision. In terms of ecosystem preference, residents indicated that the forest ecosystem is the priority ecosystem to be conserved, particularly for younger residents, respondents with high income, and those in the midland and the upstate. This could be attributed to the forest's effect on the ecosystem services that these respondents receive, particularly towards water-related ecosystem services. Understanding the residents' preference provides information that could improve the state water plans and other potential policy implications to land use-land cover planning and landscape sustainability management. Abstract : Ecosystems ranking; Ecosystem services ranking; Stakeholder approach; Conservation planning; Preference analysis; Ranking analysis